PENGARUH GREEN MARKETING TERHADAP BRAND IMAGE DAN KEPUTUSAN PEMBELIAN AQUA DI KECAMATAN PINGGIR - Bonar Situmorang, Jeremi; Malau, Harman; Hutabarat, Francis M. (POLITEKNIK LP3I JAKARTA, 2026)
The aim of this research is to ascertain how green advertising influences brand perception and consumers’ purchasing decisions for AQUA products in Pinggir District. In addition, the role of brand image as a factor affecting this relationship is also examined. This research utilizes a quantitative methodology through the distribution of questionnaires to 150 respondents who have previously purchased and used AQUA products. A Likert scale ranging from 1 to 5 is used in this research. The results of the study show that with r2 of 0.791, green advertising has a significant influence on brand image. The results also show that brand image also has a positive and significant effect on consumers’ purchasing decisions for AQUA products, with an R² value of 0.747. The research indicates that brand image serves as a mediating variable in the correlation between green advertising and consumer purchasing decisions. In this case, AQUA functions as a full mediator that bridges this relationship. Overall, the results suggest that AQUA’s green marketing strategy is highly dependent on its integration with efforts to enhance consumers’ brand perception.